GREEN SYNTHESIS OF SPIRULINA OIL-BASED NANOVESICLES AS A BIOENHANCER FOR THE INTRANASAL BRAIN TARGETING OF STATINS: CELL LINE STUDY ON HUMAN BRAIN CANCER CELL SNB-75 AND PHARMACOKINETICS ON RATS - ELTAHAN, MAHMOUD; BAKER, DOHA H. ABOU; ABBAS, HEBA S.; ABDELMONEM, REHAB; EL-NABARAWI, MOHAMED; ATTIA, ALSHAIMAA (International Journal of Applied Pharmaceutics, 2025)
Objective: This study presents a novel glioma treatment strategy using intranasally administered statin-loaded Spirusomes, integrating Spirulina oil as a bioenhancer to potentiate statins’ anticancer effects, optimize bioavailability, and minimize systemic exposure. Methods: Eight atorvastatin-loaded Spirusome formulae were prepared and assessed concerning vesicle size, charge, entrapment efficiency, and in vitro release profile. F1, containing 10 mg of atorvastatin, 100 mg of lecithin, and 1 mg of Spirulina oil, achieved a desirability score of 0.859 based on Design Expert® analysis. Raman spectroscopy was used to test for any possible drug interactions. In vitro cytotoxicity studies on SNB-75 human brain cancer cells were carried out to evaluate the anticancer efficacy of the optimized Spirusomes. In vivo pharmacokinetic studies on albino rats were used to examine the drug’s pharmacokinetic profile in plasma and brain tissues after intranasal and oral administration. Results: The optimized formula (F1) achieved nearly complete drug release within 24 h, with no drug interactions confirmed via Raman spectroscopy. In vitro cytotoxicity studies showed an IC50 of 39.48±2.01 µg/ml for atorvastatin-loaded Spirusomes, which was lower than that for plain atorvastatin. In vivo pharmacokinetics revealed a 7-fold increase in brain bioavailability (AUC0-24 = 4660.685±216.849 ng. h/gm), indicating enhanced selectivity following intranasal administration. Conclusion: This investigation reveals that atorvastatin-loaded Spirusomes might serve as an effective and selective delivery system for brain cancer treatment. The optimized formula demonstrated excellent physicochemical properties, efficient drug release, potent anticancer activity, and promising pharmacokinetics, indicating substantial preclinical potential as a brain-targeted drug delivery system. However, further studies employing glioma-bearing animal models are necessary to evaluate therapeutic efficacy and validate these findings in a disease-relevant context.